2021
DOI: 10.9734/jpri/2021/v33i37b32016
|View full text |Cite
|
Sign up to set email alerts
|

Deep Margin Elevation for Indirect Restorations: A Systematic Review

Abstract: Background: The evolution of adhesive dentistry has increased the demand for improving the clinical outcomes of indirect restorations. There are several challenging factors in restoring teeth with deep interproximal lesions. Surgical crown lengthening has been the primary procedure to avoid violation of the biological width. In recent years, deep marginal elevation (DME) has been proposed as an alternative procedure for maintaining biological width in cases with subgingival defects. The aim of this review was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Figure 1 shows the results of the study selection process, which led to the inclusion of seven review articles, 4,13–18 six reports of clinical investigations, 19–24 24 reports of in vitro/in silico studies, 7,7,25–47 and one report of a dental healthcare survey 48 . Data extracted from these 38 articles are reported in detail in Tables 1, 2, 3, and 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the results of the study selection process, which led to the inclusion of seven review articles, 4,13–18 six reports of clinical investigations, 19–24 24 reports of in vitro/in silico studies, 7,7,25–47 and one report of a dental healthcare survey 48 . Data extracted from these 38 articles are reported in detail in Tables 1, 2, 3, and 4.…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven review articles that included a systematic literature search, five articles were classified as systematic reviews 13,14,16–18 and one article included a meta‐analysis 14 . The risk of bias of included studies was assessed in two review articles, which found a high risk of bias in five out of six included studies and four out of nine included studies, respectively 17,18 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the forced orthodontic eruption of the tooth is contraindicated in cases with inadequate crown-root ratio or cases of lack of occlusal clearance for the required amount of eruption [ 19 ]. Deep margin elevation (DME) techniques have been proposed to for indirect restorations [ 20 ]. These are the available concepts for the management of SCTA width violations.…”
Section: Discussionmentioning
confidence: 99%
“…Proper tooth isolation and the use of composite resin are essential steps in these clinical procedures to avoid SCTA width violations [ 20 ]. Additionally, the R2-technique for deep occlusal-proximal resin composite restorations has been shown to prevent gingival and periodontal inflammation when the restoration margins do not violate the SCTA width [ 21 ] (Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, using one of deep margin elevation (DME) or coronal margin relocation (CMR) has been advocated as an alternative procedure to avoid the violation of biological width in cases with subgingival defects in certain clinical situations. [10]. Furthermore, for the treatment of large cavities, direct and indirect adhesive restorations are used, and these restorations require a dry working field, which can be achieved via a less invasive approach of DME.…”
Section: Introductionmentioning
confidence: 99%